Making Intergroup Contact More Fruitful: Enhancing Cooperation Between Palestinian and Jewish-Israeli Adolescents by Fostering Beliefs About Group Malleability. (January 2017) - Goldenberg, Amit; Endevelt, Kinneret; Ran, Shira; Dweck, Carol S.; Gross, James J.; Halperin, Eran
For decades, increasing intergroup contact has been the preferred method for improving cooperation between groups. However, even proponents of this approach acknowledge that intergroup contact may not be effective in the context of intractable conflicts. One question is whether anything can be done to increase the impact of intergroup contact on cooperation. In the present study, we tested whether changing perceptions of group malleability in a pre-encounter intervention could increase the degree of cooperation during contact encounters. Jewish and Palestinian-Israeli adolescents ( N = 141) were randomly assigned either to a condition that taught that groups are malleable or to a coping, control condition. During a subsequent intergroup encounter, we used two behavioral tasks to estimate the levels of cooperation. Results indicated that relative to controls, participants in the group malleability condition showed enhanced cooperation. These findings suggest new avenues for enhancing the impact of contact in the context of intractable conflicts.